Implementation of Application Based Management of Basic Education Data (DAPODIK) in Elementary Schools - Ramdanil Mubarok; Mohd. Samran (Journal of Elementary Education Research and Practice, 2025)
Efficient management of education data is essential to improve the quality of education in Indonesia. In the digital era, the Basic Education Data System (Dapodik) has become the leading innovation in collecting and managing education data nationally. This research examines the implementation of Dapodik at SD IT Syekh Yusuf South Sangatta, which has not been discussed much in previous studies. The research analyses the benefits, challenges, and strategies for implementing Dapodik in schools. The method used is qualitative research with a case study approach, collecting data through observation, interviews and documentation with school principals, Dapodik operators and teachers. Data analysis was carried out using the Miles and Huberman interactive model. The research results show that implementing Dapodik at SD IT Syekh Yusuf South Sangatta requires an integrated approach that refers to the management function POAC (Planning, Organizing, Implementing and Controlling). Careful planning stages, structured team organization, routine data input, and regular evaluation are important factors to support the efficiency and accuracy of educational data management. These findings contribute to developing technology-based education management and can be a reference for other schools in optimizing Dapodik. Applying the POAC theory can create a more efficient and accurate educational information system.